THE POSSIBILITIES OF APPLYING HEDGING STRATEGIES ON INTERNATIONAL COMMODITY EXCHANGES - Janković, Irena; Kovačević, Vlado; Zakić, Vladimir (International Journal of Economic Practice and Policy, 2019)
The aim of the paper is to determine the possibilities of implementing hedging strategies of Serbian agricultural producers on foreign commodity exchanges. Considerable fluctuations in prices of agricultural products in Serbia create the need for the use of futures in commodity exchanges in order to protect against unfavourable change in prices of agricultural products in the future period. Due to the fact that Serbia has not established the trading in commodity derivatives, Serbian producers are having to use developed commodity exchanges abroad. The paper analyses the possibilities of using the Chicago Mercantile Exchange in the USA and the MATIF commodity exchange in Paris, looking at two aspects of the activities. First, the correlation of corn prices on domestic and foreign commodity exchanges was investigated, given that it is the basic prerequisite for the application of successful hedging strategies and, secondly, legal requirements, primarily tax policies related to trade of futures contracts. This paper has found that there is a high correlation between the crops price in the foreign commodity markets and spot market in Serbia, which provides a solid basis for the implementation of hedging strategies for underlying assets in foreign commodity markets. However, it has been found that inadequate taxation policy is an aggravating factor for the implementation of hedging strategies.